Gravitational energy harvesting system based on multistage braking technique for multilevel elevated car parking building - Al Kubaisi, Yasir Mahmood (2020)
Recently, the exploitation of renewable energy resources has been underlined in high-rise buildings and the contribution of buildings in energy conservation has witnessed increased advances in recent years in both residential and commercial sectors. Buildings account for 40% of the world’s energy consumption and the multilevel car park is a part of many of these buildings. Therefore, developing an efficient, reliable, and cost-effective systems are crucial in such high-consumption buildings. Gravitational energy has a wide historical knowledge. One of that promising improvement of electrical energy is to use the potential energy of moving-down objects in high buildings. In this work addresses exploiting the gravitational energy of moving down mass for vehicles by designing a mechanical structure named as Gravitation Energy Harvester (GEH). Applying a methodology based on three basic aspects; Firstly, designing a (GEH) structure of a scaled-down prototype for the actual system describing the mechanism of the energy harvesting, which is inspired by the elevator structures. The rotational source was offset mass was anchored on the rotor pulls and rub to create torque. This produces a relative angular speed between the rotor and stator of the DC generator, which causes the power to be generated. Secondly, developing energy optimization criteria by adopting a multistage braking system inspired by regenerative brake systems, this mechanism provides braking for the climbed down vehicles while aggregating more energy by adding electrical loads in each stage through the moving down period. Thirdly, modeling of electrical and mechanical parameters for the presented system such that the system performance matching the model, this process is performed by using a parameter optimization algorithm. For this purpose, the experimental measurements of the (GEH) structure conducted under different weights and different scenarios of operations, with and without braking mechanism. The measurements of the harvested power and energy show different profiles depending mainly on the weight values and the availability of the braking mechanism. Therefore, the presented (GEH) is able to generate 57.996 J when applying a Multi-Stage Braking System (MSBS) and 38.226 J without MSBS. The results showed that, 34.09% energy and 6.58% delay time have been improved using the proposed system and proposed optimised mass at 3.5 kg. Based on the MSBS experiment, the parameters used are being applied in developing an optimization model; both results are compared and obtained an 8.2% error. Thus, using the optimization model for estimating the real application of a high building (20 m) and vehicle mass (1500 kg) of 100 car spaces have generated 11.09 KWH harvesting energy that able to cover the electrical consumption of the parking building.